2019
DOI: 10.17796/1053-4625-43.1.3
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Customized Pulse Oximeter and Sensitivity Pulp Tests for Assessment Of Pulp Vitality

Abstract: Objective: The purpose of this study was to test a customized pulse oximeter (CPO) for evaluation of pulp vitality in primary and permanent teeth against clinical diagnosis (vital and untreated non-vital) in order to expand its clinical use for pulp preservation. Study design: CPO was evaluated on intact primary and permanent central or lateral incisor (CI, LI) teeth-vital (group 1, 20n each); untreated non-vital (group 2, 10n each) and; root filled non-vital (group 3, 10n each) of children 4–12 years accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…That result could be explained by the fact that the oxygen saturation was measured only in the maxillary anterior teeth, while in our study, measurements were taken from all maxillary teeth. Sharma et al found a strong positive relationship between the tooth and finger oxygen saturation values in the vital permanent teeth [31]. Although the age of the patients in their study was from 4 to 12 years old, no data regarding the root formation stage was specified.…”
Section: Discussionmentioning
confidence: 82%
“…That result could be explained by the fact that the oxygen saturation was measured only in the maxillary anterior teeth, while in our study, measurements were taken from all maxillary teeth. Sharma et al found a strong positive relationship between the tooth and finger oxygen saturation values in the vital permanent teeth [31]. Although the age of the patients in their study was from 4 to 12 years old, no data regarding the root formation stage was specified.…”
Section: Discussionmentioning
confidence: 82%
“…Sharma et al showed that thermal pulp test and pulse oximetry accuracy was 100% and this was 90% in electrical pulp test for permanent and 86.67% for primary teeth. 17 In a study by Dastmalchi et al 18 on 24 mature mandibular premolars, the sensitivity of pulse oximeter, cold test, and EPT was 93%, 53%, and 60%, respectively. Their specificity was 100%, 55%, and 22%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Most previous studies have focused on sensitivity and specificity of tests, but PPV and NPV are also important for clinical use of a diagnostic test. 8,15,17 In the assessment of these values, the prevalence of the disease is important because these values change with prevalence. 13 The prevalence was 52% in the study by Gopikrishna et al 6 , 39% in the study by Peterson et al 26 , and 25% in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographically, there was no periapical lesion or any adverse change with respect to 21. The patient did not respond to heat test and customised pulse-oximeter 16 gave a reading below 80, both suggestive of pulpal necrosis. Hence root canal treatment (RCT) followed by intra-coronal bleaching with 21 was planned.…”
mentioning
confidence: 93%